Self-Annealing Behavior of Electroplated Cu with Different Brightener Concentrations. Issue 8 (20th May 2020) - Yang, Cheng-Hsien; Lee, Yu-Wei; Lee, Cheng-Yu; Lee, Pei-Tzu; Ho, Cheng-En
Abstract : The self-annealing (room-temperature annealing) behavior of electroplated Cu has recently received a great deal of attention from the microelectronics industry because its remarkable microstructure transition is closely related to several crucial reliability issues, including substrate warpage, pinhole formation, corrosion, and electrical resistivity. Organic additives (e.g., brightener and leveler) in the electrolyte are indispensable for the superfilling of electroplated Cu in blind-/through-hole structures, and their effects on the Cu self-annealing behavior should be quantitatively characterized. We investigated the effect of brightener concentration ( C b ) on the crystallographic transition of electroplated Cu (including the evolutions of the grain size, grain boundaries, and grain orientation) by means of X-ray diffraction (XRD), electron backscatter diffraction (EBSD), and high-resolution transmission electron microscopy (HRTEM) during self-annealing. Furthermore, the mechanical properties of electroplated Cu (hardness and Young's modulus) resulting from different C b were investigated through nanoindentation testing. The concentration depth profiles of the impurities (Cl, N, C, and S) in the electroplated Cu were characterized by time-of-flight secondary ion mass spectrometry (TOF-SIMS). These investigations showed that C b is a dominant factor of the Cu self-annealing behavior and mechanical properties, and a sufficient C b is required for the initiation of a remarkable crystallographic transition even at room temperature.